Synthesis of potential HIV integrase inhibitors inspired by natural polyphenol structures. Issue 16 (18th August 2018) - Righi, Giuliana; Pelagalli, Romina; Isoni, Valerio; Tirotta, Ilaria; Marini, Martina; Palagri, Matteo; Dallocchio, Roberto; Dessì, Alessandro; Macchi, Beatrice; Frezza, Caterina; Forte, Gianpiero; Dalla Cort, Antonella; et al.
Abstract: Drawing inspiration from the structural features of some natural polyphenols, the synthesis of two different model compounds as potential inhibitors of HIV integrase (IN) has been described. The former was characterised by a diketo acid (DKA) bioisostere, such as a β-hydroxycarbonyl moiety, between two fragments containing aromatic groups, while in the latter an epoxide linked two polyoxygenated aromatic residues. The moieties present in the structures are thought to function by chelating divalent metal ions on the enzyme catalytic site. Overall, 10 compounds were prepared and some of that submitted to molecular modelling studies (to investigate their interactions with the active site of IN), to metal titration studies (to detect their chelating capability) and to biological assays. Abstract :